2014
DOI: 10.1111/bcpt.12335
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory Effect of Rosmarinic Acid and an Extract of Rosmarinus officinalis in Rat Models of Local and Systemic Inflammation

Abstract: Rosmarinic acid is a polyphenolic compound and main constituent of Rosmarinus officinalis and has been shown to possess antioxidant and anti-inflammatory properties. We aimed to evaluate the anti-inflammatory properties of rosmarinic acid and of an extract of R. officinalis in local inflammation (carrageenin-induced paw oedema model in the rat), and further evaluate the protective effect of rosmarinic acid in rat models of systemic inflammation: liver ischaemia-reperfusion (I/R) and thermal injury models. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
161
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(175 citation statements)
references
References 75 publications
7
161
1
6
Order By: Relevance
“…Literature review revealed that rosmarinic acid and its derivatives have been shown to have biological activities, which included: antiinflammatory [8], anti hyperglycemic [9],anti allergic [10], anti bacterial activity [11], anti-oxidant [12], in addition those have beneficial effect in Parkinson's disease [13], neuroprotective effect [14], and also have nephroprotective activity belong to their antioxidant potency through enhancing the activity of antioxidant enzymes and enhancing the glutathione content [15]. R. officinalis contains a great quantity of essential oil that formed from chemical components; these are hydrocarbon monoterpenes (e.g., camphene, pinene, limonene, and myrcene), sesquiterpenes (e.g., caryophyllene), and oxygen deravatives such as alcohols (e.g., borneol, linalool, and terpineol), ketones (e.g., camphor and verbenone), oxide (e.g., 1, 8-cineole), esters (e.g., bornyl acetate), and others [16].…”
Section: Introductionmentioning
confidence: 99%
“…Literature review revealed that rosmarinic acid and its derivatives have been shown to have biological activities, which included: antiinflammatory [8], anti hyperglycemic [9],anti allergic [10], anti bacterial activity [11], anti-oxidant [12], in addition those have beneficial effect in Parkinson's disease [13], neuroprotective effect [14], and also have nephroprotective activity belong to their antioxidant potency through enhancing the activity of antioxidant enzymes and enhancing the glutathione content [15]. R. officinalis contains a great quantity of essential oil that formed from chemical components; these are hydrocarbon monoterpenes (e.g., camphene, pinene, limonene, and myrcene), sesquiterpenes (e.g., caryophyllene), and oxygen deravatives such as alcohols (e.g., borneol, linalool, and terpineol), ketones (e.g., camphor and verbenone), oxide (e.g., 1, 8-cineole), esters (e.g., bornyl acetate), and others [16].…”
Section: Introductionmentioning
confidence: 99%
“…Rosmarinic acidhas a wide range of health benefited biological properties i.e., anti-inflammatory, antioxidant and so on those were reported by (Domitrović et al, 2013;Rocha et al, 2015).…”
Section: Introductionmentioning
confidence: 89%
“…[6][7][8][9] However, to the best of our knowledge, there are no reports about the potential effects of caffeic acid, myristicin and rosemarinic acid on the gene expression and production of mucin from airway epithelial cells. Among the twenty one or more MUC genes coding human mucins reported up to now, MUC5AC was mainly expressed in goblet cells in the airway surface epithelium.…”
Section: -4mentioning
confidence: 99%